Exchange Rate Risk and Exchange Rate Risk Management in Lithuania - Kaupys, Rolandas (Ekonomika, 2003)
In nowadays highly competitive business world risk management became one of the major areas of academic and professional research. Exchange rate risk management became extremely important in 1980’s when major currency exchange rates were set to float. In Lithuania, exchange rate risk management became relevant when national currency litas was introduced and Lithuania became an active participant in international trade.Exchange rate risk can be looked at under three separate headings: transaction risk, economic risk and accounting risk. Transaction risk arises when company’s cash flows arc denominated in different currencies and exchange rate of the currencies fluctuates. Transaction risk makes the greatest influence on company’s value and profits.Research of Lithuania’s currency market suggests that derivatives market compounds only a small fraction of whole market activity. Lithuanian legal entities rarely if ever use currency derivatives to manage exchange rate risk.However, market for currency derivatives have shown a substantial growth over the period from 1999 to 2003 year. Noteworthy that market for currency options made up a major part of whole derivatives market from 1999 to 2001 year. The reason for that could have been ineffective regulation of calculating open foreign currencies positions in Lithuanian commercial banks. As order of open foreign currency positions calculation was changed by Lietuvos bankas at the beginning of 2002 year, options trading volumes declined by large amount. The structure of Lithuania’s derivatives market from the beginning of 2002 year could be viewed as under normal market conditions.An original exchange rate risk management model was established at the and of this article. Lithuanian companies are highly recommended to use this model to manage exchange rate risk. Major steps of this model are calculation of open foreign currencies positions, choice of exchange rate risk management policy and appropriate instruments.Meaningful definitions: exchange rate risk, exchange rate risk management, currency derivatives, forward contract, future contract, swap contract, option contract.